Developing and introducing a post birth care plan (PBCP): An action research project. (March 2020) - Crowther, Susan; Lau, Annie; MacIver, Emma
Highlights: A post birth care plan (PBCP) has been developed through collaboration with women and community midwives. Seven themes emerged from interviews that informed the format of a PBCP template. A PBCP contributes to individualised sensitive care. PBCPs could be especially beneficial when there is fragmentation of services. Women and midwives recognise the benefit of using a PBCP. Abstract: Objective: There is ongoing poor evaluation of post-birth care and an urgent need to improve women's satisfaction. To develop and evaluate an acceptable and useable post-birth care plan template through collaboration with women and community midwives. Design: Qualitative methodology using an action research design. Setting and participants: North East Scotland. 10 pregnant women and 6 community midwives. Findings: Seven themes emerged from thematic analysis that informed the format of the PBCP template: being prepared for transitions, physical needs, psychosocial needs, cultural, religious and spiritual needs, organisation of care information, knowledge transfer, financial information and guidance. Key conclusions: Women and midwives recognised the benefit of using a PBCP to ensure all information is covered and that care is individualised and organised according to cultural, social and physical needs, especially when there is fragmentation of services. The open conversational style of the PBCP provides opportunity to explore post-birth needs and how they develop over time. Implications for practice: PBCPs provide an opportunity for women to explore their post-birth needs with their midwife, enabling them to have meaningful, respectful conversations with their midwives during the antenatal and post-birth period. This has the potential to increase women's satisfaction with their care and is particularly pertinent in regions where fragmentary systems of care are prevalent.